Biopsy needles for mediastinal lymph node sampling by endosonography: current knowledge and future perspectives - Colella, Sara; Scarlata, Simone; Bonifazi, Martina; Ravaglia, Claudia; Naur, Therese Maria Henriette; Pela, Riccardo; Clementsen, Paul Frost; Gasparini, Stefano; Poletti, Venerino (Journal of Thoracic Disease; Vol 10, No 12 (December 30, 2018): Journal of Thoracic Disease, 2018)
Due to the increasing role of endosonography [endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) and esophageal ultrasound-guided fine needle aspiration (EUS-FNA)] in the diagnosis of several lung diseases, the knowledge of technical aspects is mandatory to optimize the success of the procedure. Among those technicalities related to the procedure, the choice of a needle over another one—either in terms of dimension and type—may have a role in the diagnostic process, especially in some diseases such as lymphoproliferative disorders. In this review, we analyze the current knowledge about the biopsy needle for endosonography, providing also some hints for the future.